Growth potential of pacu,piaractus brachypomus in different culture approaches - Rejoice,uchoi (school of aquaculture,CoF, 2014)
Abstract- The study was conducted to evaluate the growth potential of pacu, Piaractus brachypomus in different culture approaches in monoculture and polyculture system with feeding, fertilization and substrate based system. The experiment was carried out for 90 days in outdoor circular cement cistern of 380 litre capacity. The culture strategies/treatments employed are monoculture of P. brachypomus with feeding alone (T1), Polyculture of P. brachypomus with catla, rohu and mrigal with feeding alone (T2), Polyculture of P. brachypomus with Pangasius hypophthalmus with feeding alone (T3), Monoculture of P. brachypomus, with fertilization alone (T4), polyculture of pacu in combination with Indian major carps with fertilization (T5) and polyculture of pacu in combination with Indian major carps in substrate based system (T6). Coconut spadix was used as a substrate for periphyton growth. Each treatment was done in a set of three cistren. In case of monoculture of pacu a total number of 10 fishes were stocked in each cistern. Whereas in case of polyculture of pacu, with pangas, both were stocked @ 5 nos.each species per cistern respectively. Polyculture of pacu with catla, rohu and mrigal were stocked in the proportion 3:2:3:2 respectively. In treatment involving feeding, feeding was done with locally available commercial feed with overall protein content of 30% and given at the rate of 10% of body weight and subsequent feeding rate was adjusted with increased in fish weight. In the treatments involving fertilization (T4 andT5), and substrate based system (T6) all tanks were initially fertilized with raw cow dung (150 g) in combination with 2 g of urea and subsequent fertilization of half of the initial level was done fortnightly. Fish were sampled every fortnightly for weight and length measurements. Water quality parameters were monitored at fortnightly intervals. The water quality parameters in different treatments over the period of study were in the ranged, pH 6.8 -9, dissolved oxygen 4.0-6.0mg/l, temperature 260-29.50c, alkalinity 69.0-125.50mg/l CaCo3, ammonia 0.00- 0.5ppm, nitrite 0.00-0.5ppm, and nitrate 0.00-4ppm respectively. Significant growth increments were observed in all cultural approaches. The present study revealed that average gain in body weight of all the fish species together was more in treatment involving supplementary feed alone followed by substrate based system and fertilization alone respectively. Piaractus brachypomus recorded the highest growth in terms of gain in weight in T1 (Monoculture of pacu with feeding alone) and the lowest gain in weight of pacu was obtained in T4 (Monoculture of pacu with fertilization alone). In monoculture of pacu, T1 shows significantly (P<0.05) higher gain in weight compare to T4 (culture of pacu alone with fertilization). In case of polyculture of pacu with different species combination, T3 (Culture of pacu with Pangas with feeding) shows higher gain in weight followed by T2 (Culture of pacu with IMC with feeding), T6 (Culture of pacu with IMC in substrate based system) and T5 (polyculture of pacu with IMC with fertilization alone) respectively. Survival rate of pacu was good in all treatment with average value ranging from 80 (T3) to 100% (T6). Inclusion of pacu along with pangas, catla, rohu and mrigal not appears to have impact on their survibility rate. SGR of pacu ranged between 2.46% and 3.10 %. Food conversion ratio (FCR) of P. brachypomus in different treatments ranged between 1.81 and 2.12. Sensory evaluation of organoleptic qualities of raw and cooked pacu fillet with respect to colour, odour and texture remains non- significance (p<0.05), whereas sensory evaluation of cooked pacu fillet only taste shows significance difference (p<0.05), in all the treatments. The present study shows that the best growth performance of P. brachypomus was in monoculture with feeding followed by culture of pacu with pangasius with feeding. In case of polyculture with Indian major carps best growth performance of P. brachypomus was obtained in polyculture with Indian major carps with feeding followed by substrate based system. Thus from the study we can conclude that pacu is a promising species in freshwater aquaculture. Monoculture of pacu is a feasible approach whereas monoculture in fertilized systems is less productive Pacu is a compatible species for culturing along with Indian major carps. Growth of pacu is higher in fertilized systems with added substrates.